Cryoprotective properties of organic compounds in water solutions - Roshal, A.D.; Dyubko, T.S.; T.P. Linnik, T. P. (Biophysical Bulletin, 2005)
4'-Dimethylaminoflavonol (DMAF), a fluorescent probe for phase-to-phase transfer detection has been used for prediction of cryo-protective properties of organic solvents. It has been found that hypsochrome shift of probe emission band and its fluorescence intensity growth upon cryo-protector (CP) addition correlates with CP lipophility parameter and with CP cytotoxicity. Semi-resolvation concentration values obtained by titration of DMAF water solutions with cryo-protectors correlates with cryo-protective activity of these last. This correlation exists if this CP activity bases on the effect of partial resolvation of cell membrane hydrate layer. Results, which have been obtained with DMAF, correspond well to the experimental data concerning cell cryo-conservation.